2019
DOI: 10.3906/sag-1809-100
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of MEFV mutations in Turkish FMF patients: multicenter study representing results of Anatolia

Abstract: Background/aim: The distribution of Mediterranean fever (MEFV) gene mutations in Turkish familial Mediterranean fever (FMF) patients varies according to geographic area of Turkey. There is a need for highly representative data for Turkish FMF patients. The aim of our study was to investigate the distribution of the common MEFV mutations in Turkish FMF patients in a nationwide, multicenter study. Materials and methods: Data of the 2246 FMF patients, from 15 adult rheumatology clinics located in different parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 27 publications
1
7
1
1
Order By: Relevance
“…In our study, it was observed that there was a decrease in the frequency and number of attacks in almost all patients treated with canakinumab, consistent with previous efficacy studies. In addition to the frequency of attacks, a significant decrease was also shown in acute-phase reactants with IL-1 antagonists, similar to our results [ 8 , 20 , 23 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, it was observed that there was a decrease in the frequency and number of attacks in almost all patients treated with canakinumab, consistent with previous efficacy studies. In addition to the frequency of attacks, a significant decrease was also shown in acute-phase reactants with IL-1 antagonists, similar to our results [ 8 , 20 , 23 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Four of the five most common mutations occur in exon 10 (M694V, V726A, M694I, M680I), and one in exon 2 (E148Q). According to the genotype, homozygous M694V (24%) was the most common mutation, followed by heterozygous M694V in Turkish MFF patients [ 8 ]. Mutations disrupt pyrin regulation, resulting in caspase-1 activation, which mediates the release of interleukin-1ß (IL-1β) from its inactive precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we had no data regarding the MEFV gene mutation status of the patients. However, it is thought that the MEFV gene mutations of the patients in this study are not different from MEFV mutations which have been shown in the literature to be mostly associated with renal amyloidosis in Turkish FMF patients 17 …”
Section: Discussionmentioning
confidence: 47%
“…Patients with the E148Q variant, which is a common variant in FMF patients in Turkey, were also included in this study. 7 …”
Section: Methodsmentioning
confidence: 99%